MORPHOLOGICAL FEATURES OF THE STRUCTURE OF THE BRONCHIAL MUCOSA IN CHILDREN (Ideal Journal of Multidisciplinary Research, 2026)
Smooth muscle (SM) of the airways develops from local mesenchymal cells located around the tips of growing epithelial buds. These cells gradually migrate from the proximal to the distal side of the bronchial tree, elongate, and begin to produce smooth muscle (SM)-specific proteins. Mechanical stress (or cell spreading and elongation) regulates epithelial paracrine factors that control bronchial muscle processes. The exact role of many of these paracrine factors in the normal development of the lungs is currently unknown.
Keywords: Morphological changes, control group, children, observation group.